Maintaining foveal fixation during a peripheral detection task. (November 2016) - Fotios, S; Uttley, J; Cheal, C
Using road lighting to improve the detection of potential hazards may contribute to reduced accident rates for pedestrians, drivers and other road users. In past studies carried out to measure peripheral detection, the test participant was instructed to maintain fixation on a target during presentation of the peripheral target, but these studies did not question the degree to which this fixation was maintained. We therefore used eye tracking to record fixations during a peripheral detection task and introduced a fixation task designed to encourage fixation. It was found that observers were good at maintaining foveal fixation and there was little benefit in introducing a fixation task although this might be of greater benefit if the peripheral field contains more interesting distractions.